2016
DOI: 10.1108/et-10-2014-0124
|View full text |Cite
|
Sign up to set email alerts
|

Student experience of oral communication assessment tasks online from a multi-disciplinary trial

Abstract: Tuning Process in Europe (Socrates-Tempus, n.d.) and the Australian Qualifications Framework (Australian Qualifications Framework Council, 2013), require universities to demonstrate that students are assessed for generic skills such as the ability to transmit information to others. In Australia, for example, masters by research students are required to have "communication and technical skills to present a coherent and sustained argument and to disseminate research results to specialist and non-specialist audie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
6
0
3
Order By: Relevance
“…In terms of JEs, Brazil is the most dynamic country, with two-thirds of the total number of JEs in the world. Regarding sex, only in the overall EI ( F (1, 306) = 7.49; p < 0.01) there was a significant difference, where males ( N = 154) reported higher mean than females ( N = 154), which is in line with several authors who reported the influence of gender on EI (Marques et al , 2012; Shah and Soomro, 2017; Wilson et al , 2009). Finally, professional experience only significantly affects the variable ATB ( F (3, 304) = 2.91; p < 0.05), with students without professional experience ( N = 164) reporting a lower mean in this variable.…”
Section: Resultssupporting
confidence: 88%
“…In terms of JEs, Brazil is the most dynamic country, with two-thirds of the total number of JEs in the world. Regarding sex, only in the overall EI ( F (1, 306) = 7.49; p < 0.01) there was a significant difference, where males ( N = 154) reported higher mean than females ( N = 154), which is in line with several authors who reported the influence of gender on EI (Marques et al , 2012; Shah and Soomro, 2017; Wilson et al , 2009). Finally, professional experience only significantly affects the variable ATB ( F (3, 304) = 2.91; p < 0.05), with students without professional experience ( N = 164) reporting a lower mean in this variable.…”
Section: Resultssupporting
confidence: 88%
“…Likewise, most of them showed their positive attitudes towards the use of ICT to study English and expected ICT to be used more frequently in the classroom to maximize learning and language teaching. On the other hand in [15], it was found that synchronous communication leads to greater participation, also found that the incorporation of components of synchronous oral communication instead of only asynchronous traditional assessments in writing facilitates participation in the courses. Similarly, in [16] it was found that undergraduate students preferred a tool based on synchronous learning, where student-instructor interaction was the strongest predictor of student satisfaction.…”
Section: Tic Variable Summarymentioning
confidence: 99%
“…Entre las competencias comunicativas más valoradas, se sitúa la gestión integral de cualquier tipo de información (científica, técnica, legal, comercial, financiera, normativa, cultural…) (McBain et al, 2016;Ferrer, 2008), acompañada de la producción de un texto escrito (Debrine-Mascle, 2013) y su eventual exposición oral en contextos interpersonales, grupales, mediáticos, formales o informales, dialogados o monologados, etc. (Jackson, 2014;Salas-Velasco, 2012).…”
Section: Introductionunclassified